(untitled) (Psychology Travelogs, 2025)
The article examines the psychological characteristics of the teaching process in wartime as a response to the complex and many-sided experience of students. The authors are analyzing the impact of crisis, in particular stress factors, traumatic experiences caused by war, occupation, migration, etc., on the mental and emotional condition of the participants in the learning process, alongside with the changes that had occurred in the social structure of the students’ audience, the one of Kherson National Technical University in particular. The main challenges and needs of students with varying degrees of trauma are identified: from indirect trauma through the media to direct exposure to combat zones or the loss of loved ones, which requires a case-specific approach to teaching. It has been established that, under conditions of war, anxiety, difficulty focusing, emotional lability, and sleep disturbances are increasing, directly affecting motivation and the quality of learning. The article gives some effective psychological and pedagogical practices, that contribute to supporting the education in crisis conditions, and provides systematization of the best practices. There has been revealed the transformation of the teachers’ role from a knowledge transmitter to a facilitator who integrates psychological support into the educational process based on a trauma-sensitive approach. The need for teachers to develop emotional intelligence, active listening skills, and the ability to recognize signs of psychological distress in students is justified. A systematic model for adapting the educational environment to the multifaceted experience of learners is proposed, with challenges by categories of learners and teachers to have been classified and ranked according to their critical impact on the students’ mental and emotional condition. The model includes practical recommendations for creating a psychologically safe educational environment through the integration of psychological support into the teaching process. Each item in the model has a clear and accurate nomenclature identification for a further use. The conclusions emphasize the need for targeted psychological and pedagogical training of teachers enabling them to work in crisis situations, helping them develop their emotional self-regulation skills and knowledge how to use resource-related technologies. The article outlines the prospects for further research in designing specialized teacher’s training programs and creating post-war education models focused on the society rebuilding and development.